A tale of two crises: affective polarization in Greece - Nezi, Roula (Frontiers in Political Science, 2024)
Affective polarisation, the strong feelings of animosity towards the supporters of the opposite party, is rising in Europe. This study is examining the impact of policy preferences towards the measures taken to overcome the economic and the health crises on affective polarisation. The analysis reveals that both policies have an impact of affective polarisation but there are asymmetries on how policy preferences influence it. For the supporters of the governing conservative party, affective polarisation appears to be policy-driven, whereas for the supporters of the opposition, the populist left-wing party SYRIZA, it is predominantly ideology-driven. Interestingly, the supporters of the governing party continue to align with the pro-memorandum stance even in the absence of an actual memorandum.